Exploring In-Service TEYL Teachers’ Assessment Literacy: Implication For Continuing Professional Development - Umam, Amalul; Indah, Yani Awalia (Universitas Muhammadiyah Sidoarjo, 2020)
Assessment is central and holds essential role in language learning from which the result of the teaching and learning are derived. It shows that the ability of language teachers in assessing their students is crucial. This study explored the assessment literacy of in-service TEYL teachers in Bogor by employing narrative case study. The subjects of the study were 19 English teachers around Bogor. In collecting the data, CALI (Classroom Assessment Literacy Inventory) and FGD (Focus Group Discussion) were employed. The data gathered from CALI were then scored and analyzed, and FGD data were coded based on the assessment literacy standards from which conclusion were derived. The findings reveal that teachers have poor level of assessment literacy. Consequently, teachers must update themselves by conducting continuing professional development. HIGHLIGHTS: Assessing Young Learners is complicated and challenging for Indonesian teachers because of the demand of the Curriculum 2013. Assessment literacy is central in English language learning from which teachers can assess their students and communicate the results to the stakeholder. Continuing Professional Development is an important action that can be done by teachers to increase their assessment literacy.